A Big Five facet analysis of sub‐clinical narcissism: Understanding boldness in terms of well‐known personality traits. (14th April 2014) - Furnham, Adrian; Crump, John
ABSTRACT This study aimed to examine a Big Five 'bright‐side' analysis of a sub‐clinical personality disorder, i.e. narcissism. A total of 6957 British adults completed the NEO‐PI‐R, which measures the Big Five Personality factors at the domain and the facet level, as well as the Hogan Development Survey (HDS), which has a measure of Narcissism called Bold as one of its dysfunctional interpersonal tendencies. Correlation and regression results confirmed many of the associations between the Big Five domains and facets (NEO‐PI‐R) and sub‐clinical narcissism. The Bold (Narcissism) scale from the HDS was the criterion variable in all analyses. Bold individuals are disagreeable extraverts with very low scores on facet Modesty but moderately high scores on Assertiveness, Competence and Achievement Striving. The study confirmed work using different population groups and different measures. Copyright © 2014 John Wiley & Sons, Ltd.